Pengembangan Buku Cerita Bergambar Berbasis Metakognitif untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Sekolah Dasar - Putri Gupurli; Octavian Muning Sayekti; Dea Iintri Oktriyanti (Jurnal Ragam Pengabdian, 2026)
This study aimed to develop and evaluate a metacognitive picture storybook designed to improve the reading comprehension skills of fourth-grade elementary school students. Reading comprehension is an essential skill that requires engaging learning materials tailored to students’ developmental characteristics. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Participants consisted of one fourth-grade teacher, three students in the one-to-one trial, eight students in the small-group trial, twenty-three students in the large-group trial, and thirty-four students in the effectiveness test. The findings demonstrated that the metacognitive picture storybook was highly valid, practical, and effective. Validation results showed scores of 92.29% from the material expert and 92.50% from the media expert, indicating excellent validity. Teacher responses revealed practicality scores of 94.37% in the one-to-one trial and 100% in both the small- and large-group trials. Student responses reached 83.33%, 83.75%, and 94.78%, respectively, all categorized as highly practical. Furthermore, the paired-samples t-test produced a significance value of 0.000 (p < 0.05), indicating a significant improvement in students’ reading comprehension skills after using the storybook. These results confirm that the developed metacognitive picture storybook is suitable and effective for supporting reading comprehension learning in elementary schools.